PS-BPB04-6: PROOF OF BIOLOGICAL ACTIVITY AND EXPLORATION OF EARLY SIGNALING EVENTS OF ANGIOTENSIN-(1–5). (January 2023) - Silva, Igor Maciel Souza; Peluso, Antonio Augusto; Jakobsen, Lene Andrup; Jensen, Pia; Ribeiro, Lucas Rodrigues Aguiar; Mortensen, Christina; Sumners, Colin; Braga, Thiago Verano; Larsen, Martin Roessel; Steckelings, Ulrike Muscha
Abstract : Introduction: Recombinant human ACE2 increases the circulating levels of angiotensin-(1–5) [Ang-(1–5)], a peptide thus far regarded as biologically inactive. Since ACE2 is a central component of the protective RAS, we hypothesized that Ang-(1–5) is a new biologically active peptide within this hormonal system. Objective: To investigate biological activity and signaling mechanisms of Ang-(1–5). Methods: In order to show a biological effect and to test whether Ang-(1–5) signals through the AT2 -receptor (AT2 R), nitric oxide (NO) release was measured by DAF-FM fluorescence in AT2 R transfected (AT2 R-CHO) or non-transfected (NT-CHO) CHO cells, treated with Ang-(1–5) or C21 (AT2 R agonist, positive control) (0.1 nM to 10 μM) for 15 minutes. Vehicle (cell media) treated cells served as negative control. To investigate Ang-(1–5) signaling patterns, human aortic endothelial cells (HAEC) were treated with vehicle or Ang-(1–5) (1 μM) for 1, 3, 5 or 20 minutes. Proteins were harvested, digested and labeled with TMTpro-16plex. Phosphopeptide enrichment was carried out by TiO2. Samples were subjected to LC-MS/MS analysis and the resulting mass spectra were searched against the human SwissProt database. Results: Ang-(1–5) induced a concentration-dependent increase in NO production in AT2 -CHO cells (Emax: 65.60 ± 14.02%), thus proving its biological activity. Ang-(1–5) had 69% higher efficacy than the established AT2 R agonist C21 (Emax: 38.76 ± 10.24%). Ang-(1–5) seems to signal through the AT2 R, because effects on NO release were absent in NT-CHO cells. Treatment of HAEC with Ang-(1–5) significantly modified the phosphorylation status of 831 proteins at 1799 residues. The majority of residues (1079) were dephosphorylated while 729 residues were phosphorylated. Changes in protein phosphorylation in response to Ang-(1–5) occurred at all investigated time points, most of them after 20 minutes. Functional bioinformatic analysis revealed a cluster of proteins involved in cell cycle and cell division regulation. Conclusion: This study provides evidence that Ang-(1–5) is an endogenous AT2 R agonist with high efficacy towards the AT2 R. The early signaling phosphorylation pattern resembles those of other protective RAS agonists, such as C21 and Ang-(1–7).